Roles of Myeloid and Lymphoid Cells in the Pathogenesis of Chronic Obstructive Pulmonary Disease - Ni, Ling; Dong, Chen (Frontiers in Immunology, 2018)
Chronic obstructive pulmonary disease (COPD) is currently the third largest cause of human mortality in the world after stroke and heart disease. COPD is characterized by sustained inflammation of the airways, leading to destruction of lung tissue and declining pulmonary function. The main risk factor is known to be cigarette smoke currently. However, the strategies for prevention and treatment have not altered significantly for many years. A growing body of evidences indicates that the immune system plays a pivotal role in the pathogenesis of COPD. The repeated and progressive activation of immune cells is at least in part the source of this chronic inflammation. In this review paper, we have conducted an extensive literature search of the studies of immune cells in COPD patients. The objective is to assess the contributions of different immune cell types, the imbalance of pro/anti-inflammatory immune cells, such as M1/M2 macrophages, Tc1/Tc10 and Th17/Treg, and their mediators in the peripheral blood as well as in the lung to the pathogenesis of COPD. Therefore, understanding their roles in COPD development will help us find the potential target to modify this disease. This review focuses predominantly on data derived from human studies but will refer to animal studies where they help understand the disease in humans.